Should maternal anesthesia delay breastfeeding? A systematic review of the literature - Oliveira,Morenna Ramos e (2019)
Abstract Introduction: The importance and benefits of breastfeeding for the babies and mothers are well established and documented in the literature. However, it is frequent that lactating mothers need to undergo general or spinal anesthesia and, due to the lack of information, many of them interrupt breastfeeding after anesthesia. There are limited data available regarding anesthetics transfer to breast milk. This review aims to develop some considerations and recommendations based on available literature. Methods: A systematic search of the literature was conducted by using the following health science databases: Embase, Lilacs, Pubmed, Scopus, and Web of Science. The latest literature search was performed on April 6th, 2018. Additional literature search was made via the World Health Organization's website. We used the following terms for the search strategy: "Anesthesia" and "Breastfeeding", and their derivatives. Results: In this research, 599 registers were found, and 549 had been excluded by different reasons. Fifty manuscripts have been included, with different designs of studies: prospective trials, retrospective observational studies, reviews, case reports, randomized clinical trials, case–control, and website access. Small concentrations of the most anesthetic agents, are transferred to the breast milk; however, their administration seem to be safe for lactating mothers when administered as a single dose during anesthesia and this should not contraindicate the breastfeeding. On the other hand, high-doses, continuous or repeated administration of drugs increase the risk of adverse effects on neonates, and should be avoided. Few drugs, such as diazepam and meperidine, produce adverse effects on breastfed babies even in single doses. Dexmedetomidine seems to be safe if breastfeeding starts 24 h after discontinuation of the drug. Conclusions: Most of the anesthetic drugs are safe for nursing mothers and offer low risk to the breastfed neonates when administered in single-dose. However, high-dose and repeated administration of drugs significantly increase the risk of adverse effects on neonates. Moreover, diazepam and meperidine should be avoided in nursing women. Finally, anesthesiologists and pediatricians should consider individual risk/benefit, with special attention to premature neonates or babies with concurrent diseases since they are more susceptible to adverse effects.